2019
DOI: 10.1111/cas.13900
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin inhibits proliferation and promotes apoptosis via c‐Met/Akt/mTOR pathway in human osteosarcoma cells

Abstract: Osteosarcoma (OS) is the most common malignant bone tumor and frequently affects adolescents. Norcantharidin (NCTD), a demethylated derivative of cantharidin, has been reported to exhibit anticancer activity against various types of tumors but not human OS. The aim of the present study was to evaluate the effects of NCTD on OS cell lines (MG63 and HOS) and to explore the underlying mechanisms. In the present study, the proliferation of OS cells decreased significantly, while the apoptosis was accelerated signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Norcantharidin (NCTD), a demethylated derivative of cantharidin which is an active ingredient of TCM-Mylabris [1][2][3], is currently used clinically as an optional anticancer drug in China, because of its relatively synthesized facility, potential anticancer activity, and less side-effects such as myelosuppression, gastrointestinal and urinary tract toxicity [1][2][3][4][5]. Increasing evidences show that NCTD not only effectively inhibited the proliferation of many tumor cells in vitro and in vivo, including hepatoma HepG2 [6][7][8], SMMC-7721 [8,9] and BEL-7402 [10,11], gallbladder cancer GBC-SD cells [12,13], colon cancer CT26 and HT29 cells [14,15], breast cancer cells [16,17], leukemia K562 [18] and HL-60 cells [4,5,19], melanoma A375 cells [20], and oral cancer KB cells [21], but also decreased tumor growth and prolonged survival in animal models in vivo [17,22]. As an efficacious anticancer drug, it has been used to treat hepatic cancer, gastric cancer and leucopenia patients in China for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Norcantharidin (NCTD), a demethylated derivative of cantharidin which is an active ingredient of TCM-Mylabris [1][2][3], is currently used clinically as an optional anticancer drug in China, because of its relatively synthesized facility, potential anticancer activity, and less side-effects such as myelosuppression, gastrointestinal and urinary tract toxicity [1][2][3][4][5]. Increasing evidences show that NCTD not only effectively inhibited the proliferation of many tumor cells in vitro and in vivo, including hepatoma HepG2 [6][7][8], SMMC-7721 [8,9] and BEL-7402 [10,11], gallbladder cancer GBC-SD cells [12,13], colon cancer CT26 and HT29 cells [14,15], breast cancer cells [16,17], leukemia K562 [18] and HL-60 cells [4,5,19], melanoma A375 cells [20], and oral cancer KB cells [21], but also decreased tumor growth and prolonged survival in animal models in vivo [17,22]. As an efficacious anticancer drug, it has been used to treat hepatic cancer, gastric cancer and leucopenia patients in China for many years.…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating the effects of NCTD on OS cell lines (MG63 and HOS) in vitro and in vivo, we found that NCTD can inhibit cell cycle and induce apoptosis of human OS cells. ese effects are mediated by autophagy induction, triggering ER stress and inactivation of the c-Met/ Akt/mTOR pathway [23]. It works when the proliferation and apoptosis of normal cells are out of balance by inhibiting and then inducing apoptosis of tumor cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the research of FAM64A is inadequate; thus, the role of FAM64A in OS cells is still poorly understood. e dysregulation of intracellular signaling pathways such as Notch1, Akt, Wnt pathway, and JAK2/STAT3 was reported to be participated in the development of OS [3][4][5][6]. Xu et al found that FAM64A served as a positive regulator of STAT3, which is linked to various cancer types [7].…”
Section: Introductionmentioning
confidence: 99%